Factors affecting agriculture as guidelines for the economic development - Khalatur, Svitlana; Халатур, Світлана Миколаївна (Чернівецький національний університет імені Юрія Федьковича, 2017)
In the article the factor of influence on economic growth of agriculture in the future are given: final consumption, exports, production coast, market, inventory change, taxes, the value of state support, etc. As an important part of the national economy, agriculture has a number of specific characteristics of different activity fluctuations that directly affect the contribution of industry as a percentage of gross domestic products and the degree of the needs satisfaction of the domestic consumption of the population. High seasonality of production correlates with a significant degree of fragmentation of agricultural land to which may be added certain conditions more or less subjective factors influencing economic development realize the intense impact on the industry`s sustainable growth. It is argued that practice of economic development of agricultural based on market principles improve production efficiency taking into account all of the factors of formation of economic stability using the latest achievements of scientific and technological progress and efficient forms of organization of production and labor improving business integrated approach in the context of the institutional changes that occurred. In the economic development of the country`s agriculture the role of economic factors is crucial. У статті наведено фактор впливу на економічне зростання сільського господарства у майбутньому: кінцеве споживання, експорт, виробниче узбережжя, ринок, зміна запасу, податки, величина державної підтримки тощо. Як важлива частина національної економіки, сільське господарство має ряд специфічних характеристик різних коливань активності, які безпосередньо впливають на внесок промисловості як відсоток валової внутрішньої продукції та ступінь задоволеності потреб внутрішнього споживання населення. Висока сезонність виробництва корелює з значною ступенем роздробленості сільськогосподарських угідь, до якої можуть додаватися певні умови, більш-менш суб'єктивні фактори, що впливають на економічний розвиток, усвідомлюють сильний вплив на стійке зростання галузі. Стверджується, що практика економічного розвитку сільського господарства, заснована на ринкових принципах, покращує ефективність виробництва з урахуванням усіх чинників формування економічної стабільності з використанням новітніх досягнень науково-технічного прогресу та ефективних форм організації виробництва та вдосконалення трудового комплексу підхід у контексті інституційних змін, що відбулися. В економічному розвитку сільського господарства країни роль економічних факторів має вирішальне значення.
Фактори впливу на сільське господарство як орієнтири для його економічного розвитку
Keywords: impact factors; коефіцієнти впливу; economic development; економічний розвиток; strategy; стратегія; agriculture; сільське господарство